İŞLEMEYEN SİSTEMLERİN FONKSİYONEL OLMAYAN YANITI”: CUMHURBAŞKANLIĞI KARARNAMESİ - (:unkn) unknown (My University, 2018)
Makalede, Cumhurbaşkanlığı kararnamesi konusunda yedi yanıtüretilmiştir: (1) Cumhurbaşkanlığı kararnamesinin sınırlarının çizilme-mesi otoriter sonuçlar doğurur. (2) Cumhurbaşkanlığı kararnamesi, kuralolarak, normlar hiyerarşisinde kanunların altında yer alır. (3) Cumhur-başkanlığı kararnamesinin kapsamı 7 kural ile açıklanabilir. (4) Anaya-sa’da münhasır bir Cumhurbaşkanlığı kararnamesi alanı, kural olarakyoktur. (5) Cumhurbaşkanlığı kararnamesinin hükümsüz olması “kadük-lük” anlamına gelir. (6) Cumhurbaşkanlığı kararnamesi çıkarma yetkisi,kural olarak, devredilemez. (7) Cumhurbaşkanı yardımcısının yetkileri“caretaker” yetkilerdir.

The article produced seven responses regarding to the presidential decree: (1) Ambiguous clauses on presidential decree can induce to aut- horitarian consequences. (2) In principle, the presidential decree is under the statutes in the hierarchy of norms. (3) The scope of the presiden- tial decree can be explained with 7 rules. (4) In principle, an exclusive presidential decree area in the Constitution does not exist. (5) “Hüküm- süzlük” of the Presidential decree shall mean caducité of the decree. (6) In principle, the authority to issue a presidential decree is not transfe- rable. (7) The powers of the Vice-President are caretaker powers.
A DYSFUNCTIONAL RESPONSE OF NON-FUNCTIONING SYSTEMS: PRESIDENTIAL DECREE IN TURKEY
Keywords: Hukuk